Neonatal Jaundice Management: Knowledge, Attitude, and Practice Among Nurses and Midwives in the Northern Region, Ghana - Doreen Remember Donkor MPH; Shamsu-Deen Ziblim PhD; Edem Kojo Dzantor; Mubarick Nungbaso Asumah MPhil; Alhassan Abdul-Mumin MD, MSc, FGCP (SAGE Publishing, 2023)
Background Nurses and midwives play important role in managing neonatal jaundice and provide nursing health education to mothers on preventive and remedial measures to neonatal jaundice. However, the Knowledge, Attitudes, and Practices of nurses and midwives towards neonatal jaundice is not well understood in the Northern Region of Ghana. Aim of the study The study assessed the knowledge, attitudes, and practices of nurses and midwives towards the management of neonatal jaundice. Design and Method This is a hospital-based descriptive cross-sectional study, conducted between the periods of January 2021 to August 2021 in the Tamale Teaching Hospital, Northern Region, Ghana. Descriptive analysis such as mean, standard deviation, frequencies, and percentages were performed to give general description of the variables. Simple Pearson Chi-square test and logistic regression models were performed to test the level of associations between the outcome and independent variables and predictors for neonatal jaundice. A p -value of <.05 was considered statistically significant for the test of association. Results Among the 202 nurses and midwives, the mean age was 30.6 ± 3.8 years and majority were females (71.3%). The overall good knowledge, attitudes, and practices score towards neonatal jaundice was 69.30%, 64.90%, and 62.90%, respectively. After adjusting for other variables, good knowledge (adjusted odds ratio [AOR] = 22.41(10.21-49.18) p  < .001) and good attitude (AOR = 25(11.86-55.07) p  < .001) were positively associated with practices towards neonatal jaundice. Conclusion/Interpretation The participants demonstrated substantial knowledge, attitudes, and practices towards neonatal jaundice. However, there still exist some gaps in their knowledge, attitudes, and practices towards neonatal jaundice that need to be addressed to improve neonatal health outcomes in the study setting.